State and Trends of the Carbon Market 2007 - Capoor, Karan; Ambrosi, Philippe (World Bank, Washington, DC, 2013)
This report points out that there is a tendency to believe that the carbon market is somehow a magic bullet that will alone save the world from global warming. While the authors recognize the enormous strength and potential of the market to achieve results, it would be wise not to assume the market will provide a painless, magical way to mitigate climate change. First, the market does not set the level of a cap, policy-makers do. The market can only be a tool to help achieve that target. It cannot be a surrogate for a target and policy makes should not expect to be let off the hook from their jobs - making sensible policy. Second, policy makers need to set targets and support mechanisms that meet two massive challenges. They have the responsibility of taking into account the risks of climate change, especially on the poorest, as well as the opportunity of expanding clean development choices to meet the basic needs and aspirations of billions worldwide, many without access to electricity or clean water. Third, there is no free lunch. The exuberance of creating value - and enormous wealth - in a new market should not mask the fact that there are costs for mitigation. Fourth, the integrity of a market rests on the clarity and simplicity of its rules, the transparency of information and on institutions that guard against fraud and manipulation. Fifth, it is not fair to expect "cap-and-trade" or emissions trading to work in all sectors globally; clearly, housing and transport are sectors that do not lend themselves easily to an elegant emissions cap-and-trade approach. There may be other policies - including other market-based approaches or removal of subsidies - that may be more suitable in some contexts. Finally, a solution to urgent problem of the climate change problem will require sustained effort by all of us. Markets can, to a certain extent, accommodate the appetite that individuals and companies in Europe, Japan, North America, Australia and beyond have for carbon emission reductions that go well beyond what their law makers require of them. This high-potential voluntary segment, however, lacks a generally acceptable standard, which remains a significant reputation risk not only to its own prospects, but also to the rest of the market, including the segments of regulated emissions trading and project offsets.